Ceramic brick with photocatalytic function and preparation method thereof
By adopting a double-layer structure photocatalytic coating design on ceramic tiles, combined with spin coating technology and the use of silicone hydrophilic modifiers, the problems of insufficient photocatalytic performance and coating durability of ceramic tiles are solved, achieving It has high efficiency photocatalysis and good antifouling properties.
Patent Information
- Application Number
- CN202411507130.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
It is difficult to obtain a titanium oxide coating with high photocatalytic properties in the sintering process of existing ceramic tiles, and the coating durability and anti-fouling properties of the cold adhesion method are insufficient, which affects the photocatalytic effect.
It adopts a double-layer structure design. The first layer is a pure titanium oxide coating, and the second layer is a composite coating of silicon oxide and nano-anatase titanium oxide. The dispersion and loading capacity of the coating are improved through spin coating technology. , and add silicone hydrophilic modifiers and water-based acrylic resins to improve the durability and antifouling properties of the coating.
It significantly improves the photocatalytic effect of ceramic tiles, enhances the durability, hardness and adhesion of the coating, improves the anti-fouling performance, and reduces the impact on the decorative effect of the brick surface.
Smart Images

Figure CN119019187B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building ceramics, and in particular relates to a ceramic tile with photocatalytic function and a preparation method thereof. Background Art
[0002] Titanium oxide has been widely studied and applied as a photocatalytic material with high photocatalytic activity, good chemical stability, low cost and environmental friendliness. In the field of building ceramics, titanium oxide is used to form a photocatalytic coating on the surface of ceramic products, which can make ceramic tiles and other products have self-cleaning, air purification and antibacterial functions. Since titanium oxide has high photocatalytic performance only when it is in the anatase type, and the anatase type usually transforms into a high-temperature rutile phase between 400 ℃ and 800 ℃, thereby losing its photocatalytic activity, it is difficult to obtain photocatalytic ceramic products through a single firing under the existing ceramic tile firing process (firing temperature is about 1200 ℃). Therefore, there are currently two main methods for loading titanium oxide on the surface of ceramic tiles: (1) thermal adhesion method, that is, titanium oxide is loaded on the surface of the fired tile through an adhesive, and then fired again at a temperature below 800 ℃ to firmly adhere the titanium oxide powder to the surface of the tile. For example, rutile titanium oxide is directly added to a glaze containing a low-temperature frit and a pore-forming agent, and a glaze layer with photocatalytic function is obtained by firing at a low temperature (780 ° C, 30 min); another example is (2) the cold adhesion method, that is, titanium oxide and an adhesive are adhered to the micropores on the surface of the tile at room temperature, wherein the micropores are formed by polishing or deliberately corroding the surface of the tile. For example, nano titanium oxide, bismuth oxide, and zinc oxide are loaded in Y zeolite and diatomaceous earth, filtered and dried to prepare a photocatalyst composite powder, mixed with silica sol to prepare a composite antibacterial photocatalytic polishing liquid, and then coated on the surface of ceramic tiles; another example is to adhere an adhesive layer to the roughened surface of the tile, and then adhere a photocatalyst layer; another example is to use the surface microporous tile as the substrate, coat the silicone resin as the adhesive layer, and load 1 g / m 2 -20 g / m 2 of nano titanium oxide.
[0003] Although the photocatalytic ceramic products prepared by the thermal adhesion process have high coating adhesion strength, they have problems of low production efficiency and high energy consumption. For example, they need to be heat treated at high temperatures of 300℃-500℃ or 550℃-900℃.
[0004] For the cold adhesion process, although it avoids the high-temperature treatment process, it faces the problems of non-wear-resistant coating and non-durable photocatalytic effect. At the same time, in order to take into account the anti-fouling performance and the impact on the color of the tile, the titanium oxide coating load is limited, and the product photocatalytic effect is weak. Moreover, the cold adhesion method is currently usually combined with the polishing and waxing process of ceramic tiles. Since the anti-fouling wax on the surface of ceramic tiles (commonly known as B wax in production) is generally a hydrophobic silicone coating, and the photocatalytic effect of titanium oxide requires the help of water in the environment to produce hydroxyl radicals or superoxide radicals, the traditional hydrophobic anti-fouling layer will inhibit the full play of the photocatalytic function.
[0005] In addition, the good dispersibility of titanium oxide has a significant impact on the reliability of the production process and the photocatalytic effect of the final product, because titanium oxide is usually coated on the surface of ceramic products in the form of a dispersion. If the titanium oxide dispersion is very easy to agglomerate and settle, it is easy to clog the pipe or nozzle. More importantly, it will affect the uniformity of nano-titanium oxide powder on the surface of the product, and then affect the contact degree between nano-titanium oxide and the pollutants to be decomposed during use, greatly reducing the photocatalytic effect. At present, in actual operation, titanium oxide raw materials are in two forms: sol and powder. For sol, its dispersibility is generally good, but there are problems such as low titanium oxide solid content and inflexible regulation, high transportation cost, and expensive price; for powder form, it has the advantages of low price, easy adjustment of dispersion solid content and convenient transportation, but usually poor dispersibility, usually requires additional dispersant, which increases the complexity of the process and has an adverse effect on the appearance and photocatalytic effect of the brick surface. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art. Based on this, the first aspect of the present invention provides a ceramic tile with photocatalytic function, including a ceramic tile body and a first photocatalytic coating and a second photocatalytic coating arranged in sequence on the surface thereof, the first photocatalytic coating is a self-dispersed nano-anatase titanium oxide, and the second photocatalytic coating includes silicon oxide and self-dispersed nano-anatase titanium oxide.
[0007] First, the present invention adopts self-dispersed nano titanium oxide anatase powder (self-dispersion is essentially the same as monodispersion; self-dispersed nano titanium oxide anatase powder refers to nano titanium oxide that can be stably dispersed in a liquid phase, and many related documents such as "Synthesis, Characterization and Photocatalytic Performance Research of Self-dispersed Nano Titanium Dioxide Powder" have also been recorded, and for example, the patent document with announcement number CN113896235B and the name "A Method and Device for Preparing Monodispersed Nano Titanium Dioxide" also records the corresponding name, which belongs to a kind of existing material, and its self-dispersion feature can be achieved by surface modification of nano powder or specific preparation method, and there are corresponding products on sale in the market), which can achieve the monodispersion effect of titanium oxide powder at the nano level without the aid of dispersants and special dispersing equipment, thereby improving the photocatalytic effect, and avoiding the weakening of the photocatalytic effect by adding additional dispersants; at the same time, it can make the dispersion liquid have a higher transparency, reduce the influence on the decorative effect of ceramic brick surface after coating, and well solve the technical problem that the poor dispersion of nano titanium oxide powder leads to poor photocatalytic effect and easy influence on the decorative effect of brick surface.
[0008] Secondly, the present invention adopts a double-layer structure design of TiO2 coating + TiO2 & SiO2 coating, and a pure titanium oxide coating is used at the bottom, which can be fully filled into the holes on the surface of ceramic bricks, especially in the pits of micron size, so that the higher specific surface area of the initial brick surface can be effectively utilized to improve the distribution uniformity and load of titanium oxide on the brick surface; then the surface is covered with a composite coating of TiO2 and SiO2, which is mainly used to fill larger holes, and it can also further increase the load of titanium oxide while playing the role of filling holes and preventing pollution. In addition, since the coating formed by the self-dispersed nano titanium oxide powder used in the present invention will quickly dissolve in water and be lost after encountering water, when it is combined with silicon oxide to form a composite network, this problem can be well solved. In summary, the above-mentioned double-layer structure, on the one hand, increases the load of TiO2, an effective photocatalytic material, on the surface of ceramic bricks, and on the other hand, the composite coating of titanium oxide and silicon oxide also has the characteristics of high hardness, strong adhesion, and water resistance and non-redissolution. Moreover, in some preferred implementations, the second photocatalytic coating is formed by spin-coating a composite dispersion on the surface of the first photocatalytic coating, and the composite dispersion includes cationic silica sol and self-dispersed nano-anatase titanium oxide. Cationic silica sol compatible with self-dispersed nano-titanium oxide is selected as a binder at the same time. When the two are composited, the silica sol will cross-link to form a solid coating containing silicon oxide after drying, which can well overcome the technical problem of pure titanium oxide coating dissolving in water, and further improve the hardness and bonding strength of the coating, improve durability, and well solve the technical problems such as poor durability of photocatalytic coatings prepared by existing cold adhesion processes. When some conventional anionic silica sols are mixed with the self-dispersed nano-titanium oxide powder in water, there is a problem of easy gelation, while the use of cationic silica sol can avoid the occurrence of this problem. The reason may be that the acidic titanium oxide dispersion has good compatibility with the cationic silica sol, which avoids the instability of the silica sol system.
[0009] When the average particle size of the self-dispersed nano-anatase titanium oxide is 3 nm-10 nm, the effect is better.
[0010] In some preferred implementations, the composite dispersion also includes an organosilicon hydrophilic modifier and an aqueous acrylic resin. The titanium oxide and silica sol in the second layer of the present invention are nanoparticles in nature, and have a high specific surface area after drying. They are very easy to adsorb pigment-type pollutants during use. Therefore, the present invention abandons the conventional hydrophobic organosilicon antifouling wax water (when the traditional hydrophobic organosilicon is used as an antifouling agent on the surface of ceramic tiles, it will inhibit the photocatalytic reaction that requires the participation of water), and introduces an organosilicon hydrophilic modifier and an aqueous acrylic resin into the photocatalytic coating. The two organic additives can play a role in bonding and filling the pores between the nanoparticles, and complement the cationic silica sol, which is easy to penetrate and absorb. On the other hand, even if the TiO2 & SiO2 coating itself has an excellent hydrophilic effect, there will be a problem of weakening hydrophilicity due to the adsorption of pollutants in long-term use. The addition of the organosilicon hydrophilic modifier in the present invention can ensure the long-term hydrophilic surface of the coating; so that the ceramic tile finally obtained can better utilize the micro-water film on the surface during actual use to more easily adsorb harmful gases such as formaldehyde, provide a hydrophilic microenvironment for the photocatalytic reaction, and most importantly, can solve the problem of the hydrophobicity of traditional antifouling wax water inhibiting the photocatalytic efficiency. Among them, the above-mentioned organosilicon hydrophilic modifier can be one of polyether-modified polysiloxane, epoxy polyether-modified polysiloxane and amino polyether-modified polysiloxane.
[0011] The second aspect of the present invention also provides a method for preparing the above-mentioned ceramic tile with photocatalytic function, comprising the following steps: spin-coating a titanium oxide dispersion on the surface of the above-mentioned ceramic tile body (using the ceramic tile after surface polishing as the ceramic tile body) to form the above-mentioned first photocatalytic coating, and then spin-coating a composite dispersion on the surface of the above-mentioned first photocatalytic coating to form the above-mentioned second photocatalytic coating; the above-mentioned titanium oxide dispersion is obtained by mixing self-dispersed nano-anatase titanium oxide and water, and the above-mentioned composite dispersion includes self-dispersed nano-anatase titanium oxide, cationic silica sol and water, and also includes a silicone hydrophilic modifier and a water-based acrylic resin.
[0012] The solid content of the titanium oxide dispersion is 3%-15%, and the coating amount is 30 g / m 2 -50 g / m 2 The solid content of the cationic silica sol is 20%-30%. In the composite dispersion, the mass concentration of titanium oxide is 1%-5%, the mass concentration of silicon oxide is 6%-15%, the mass concentration of organic silicon hydrophilic modifier is 1%-3%, the mass concentration of water-based acrylic resin is 3%-5%, and the coating amount of the composite dispersion is 40 g / m 2 -80 g / m 2 .
[0013] The solid content of titanium oxide dispersion is 3%-15%. In order to achieve obvious photocatalytic effect, the concentration of dispersion cannot be too low, generally it needs to be higher than 3%. When the concentration is too high, the transparency of the dispersion will deteriorate, which will affect the color texture clarity of the brick surface. In addition, too high concentration is not conducive to its uniform distribution on the brick surface, because when the load is constant, the coating uniformity of low concentration dispersion will be better. Therefore, the solid content of titanium oxide dispersion should not be higher than 15%. For the same reason, the coating amount of titanium oxide dispersion should not be too little or too much. Considering the test effect and cost, the coating amount is controlled at 30 g / m 2 -50 g / m 2 .
[0014] The concentration of the composite dispersion (TiO2+SiO2) should take into account the mechanical strength, water resistance and photocatalytic effect of the coating after drying. The higher the silicon oxide content, the better the mechanical strength and water resistance of the coating, while the amount of titanium oxide has a decisive influence on the photocatalytic effect. On the other hand, the operability of the coating process should also be taken into account, because the composite coating is on the surface of the ceramic tile, and its finish after coating is very important. When the concentration is too high, the tile surface is prone to roughness and gloss loss due to uneven coating during the coating process. Therefore, considering the use effect and process requirements, the mass concentration of titanium oxide in the composite dispersion is 1%-5%, and the mass concentration of silicon oxide is 6%-15%. The coating amount of the composite dispersion is mainly based on meeting the gloss of the tile surface. In combination with production experience and test results, 40 g / m 2 -80 g / m 2 It is appropriate.
[0015] As organic materials, too much addition of silicone hydrophilic modifier and water-based acrylic resin will reduce the mechanical properties of the coating to a certain extent. Therefore, they should not be added too much. After many tests and effect analysis, the appropriate concentrations of each were selected, that is, the mass concentration of silicone hydrophilic modifier is 1%-3%, and the mass concentration of water-based acrylic resin is 3%-5%.
[0016] The spin coating in the above preparation method can be carried out by using a nylon fiber wheel; the fiber wheel and the brick surface quickly rub against each other under a large pressure to generate a high temperature, so that the dispersion can be quickly dried and solidified.
[0017] The beneficial effects of the present invention are as follows: the present invention forms a double-layer structure of TiO2 coating + TiO2 & SiO2 coating through spin coating, thereby improving the dispersibility, distribution uniformity and loading amount of titanium oxide on the brick surface, thereby greatly improving the photocatalytic effect of the ceramic tile; at the same time, the ceramic tile prepared by the present invention also has the advantages of good durability, high hardness, strong adhesion, long-term hydrophilicity, good anti-fouling properties, etc., and reduces the influence of coating on the decorative effect of the brick surface, which well solves the technical problems of the existing hot adhesion method and cold adhesion method, and is suitable for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Shown is a SEM micrograph of the surface of the polished glazed ceramic tile (100 times);
[0019] Figure 2 Shown is a SEM micrograph of the surface of the polished glazed ceramic tile (1000 times);
[0020] Figure 3 Shown are the surface wetting angle measurement results of the ceramic tile prepared in Example 1. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0022] In the following content, the self-dispersed nano-anatase titanium oxide with an average particle size of 5 nm was purchased from Suzhou Youzi Nanomaterials Co., Ltd. UG05; the self-dispersed nano-anatase titanium oxide with an average particle size of 10 nm was purchased from Suzhou Youzi Nanomaterials Co., Ltd. UG-TG01.
[0023] Example 1
[0024] A ceramic tile with photocatalytic function comprises a ceramic tile body and a first photocatalytic coating and a second photocatalytic coating arranged on the surface of the ceramic tile body in sequence, wherein the first photocatalytic coating is a self-dispersed nano-anatase titanium oxide with an average particle size of 5 nm, and the second photocatalytic coating comprises silicon oxide and a self-dispersed nano-anatase titanium oxide with an average particle size of 5 nm; the first photocatalytic coating is formed by spin-coating a titanium oxide dispersion on the surface of the ceramic tile body, wherein the titanium oxide dispersion is obtained by mixing self-dispersed nano-anatase titanium oxide with an average particle size of 5 nm and water; the second photocatalytic coating is formed by spin-coating a composite dispersion on the surface of the first photocatalytic coating, wherein the composite dispersion comprises cationic silica sol, self-dispersed nano-anatase titanium oxide with an average particle size of 5 nm, an organosilicon hydrophilic modifier (epoxy polyether modified polysiloxane), an aqueous acrylic resin aqueous solution, and water.
[0025] The method for preparing the ceramic tile having photocatalytic function comprises the following steps:
[0026] (1) Self-dispersible nano-anatase titanium oxide powder with an average particle size of 5 nm was mixed with deionized water at a mass ratio of 5:95, and a translucent self-dispersible titanium oxide dispersion with a solid content of 5% was obtained after stirring;
[0027] (2) Self-dispersed nano-anatase titanium oxide powder with an average particle size of 5 nm, cationic silica sol (model GOA10-25, solid content 25%, average particle size 10 nm), silicone hydrophilic modifier (epoxy polyether modified polysiloxane, model DY-ET304B), aqueous acrylic resin aqueous solution (model J-672, solid content 42%) and deionized water were mixed and stirred in a mass ratio of 3:48:3:7.14:38.86 to obtain a titanium oxide and silicon oxide composite dispersion with a titanium oxide mass concentration of 3%, a silicon oxide mass concentration of 12%, a silicone hydrophilic modifier mass concentration of 3% and an acrylic resin mass concentration of 3%;
[0028] (3) The glazed ceramic tile with polished surface is used as the ceramic tile body, wherein Figure 1 This is a SEM micrograph of the polished glazed ceramic tile surface (100 times). Figure 2 The SEM micrograph of the surface of the polished glazed ceramic tile (1000 times) shows that the surface has both large holes with a diameter of tens of microns and tiny pits of micron size formed by glaze breakage or crystal peeling during the polishing process. The prepared 5% titanium oxide dispersion was first polished and spun onto the tile surface using a nylon fiber wheel in a waxing machine, with a drop amount of 30 g / m 2The fiber wheel and the brick surface quickly rub against each other to generate a high temperature, which allows the dispersion to dry quickly. After that, the titanium oxide and silicon oxide composite dispersion prepared in step (2) is added dropwise at a rate of 40 g / m 2 After being spin-coated by a nylon fiber wheel, a ceramic tile product with high-efficiency photocatalytic ability is finally obtained.
[0029] The first photocatalytic layer is formed by spin-coating a nano-titanium oxide dispersion onto the brick surface, which can fully fill the holes in the brick surface, especially Figure 2 The titanium oxide is deposited in the micron-sized pits in the brick surface, which can effectively utilize the high specific surface area of the initial brick surface and improve the uniformity of the distribution of titanium oxide on the brick surface. The second layer of nano titanium oxide and silicon oxide composite coating mainly fills the larger holes, which not only plays a role in filling holes and preventing pollution, but also continues to increase the loading capacity of titanium oxide. At the same time, the composite coating of titanium oxide and silicon oxide has the characteristics of high hardness and strong adhesion, which improves the durability of the photocatalytic coating.
[0030] Example 2
[0031] A ceramic tile with photocatalytic function comprises a ceramic tile body and a first photocatalytic coating and a second photocatalytic coating arranged on the surface of the ceramic tile body in sequence, wherein the first photocatalytic coating is a self-dispersed nano-anatase titanium oxide with an average particle size of 10 nm, and the second photocatalytic coating comprises silicon oxide and a self-dispersed nano-anatase titanium oxide with an average particle size of 10 nm; the first photocatalytic coating is formed by spin-coating a titanium oxide dispersion on the surface of the ceramic tile body, wherein the titanium oxide dispersion is obtained by mixing a self-dispersed nano-anatase titanium oxide with an average particle size of 10 nm and water; the second photocatalytic coating is formed by spin-coating a composite dispersion on the surface of the first photocatalytic coating, wherein the composite dispersion comprises a cationic silica sol, a self-dispersed nano-anatase titanium oxide with an average particle size of 10 nm, an organosilicon hydrophilic modifier (polyether-modified polysiloxane), an aqueous acrylic resin aqueous solution, and water.
[0032] The method for preparing the ceramic tile having photocatalytic function comprises the following steps:
[0033] (1) Self-dispersed nano-anatase titanium oxide powder with an average particle size of 10 nm was mixed with deionized water at a mass ratio of 10:90, and a translucent monodispersed titanium oxide dispersion with a solid content of 10% was obtained after stirring;
[0034] (2) Self-dispersed nano-anatase titanium oxide powder with an average particle size of 10 nm, cationic silica sol (solid content 30%, average particle size 30 nm), silicone hydrophilic modifier (polyether modified polysiloxane), aqueous acrylic resin aqueous solution (solid content 42%) and deionized water were mixed and stirred in a mass ratio of 5:50:1.5:11.9:31.6 to obtain a titanium oxide and silicon oxide composite dispersion with a titanium oxide mass concentration of 5%, a silicon oxide mass concentration of 15%, a silicone hydrophilic modifier mass concentration of 1.5% and an acrylic resin mass concentration of 5%;
[0035] (3) The glazed ceramic tile with polished surface was used as the ceramic tile body. The prepared 10% titanium oxide dispersion was first polished and spun onto the tile surface using a nylon fiber wheel in a waxing machine. The amount of the dispersion was 50 g / m 2 The fiber wheel and the brick surface quickly rub against each other to generate a high temperature, which allows the dispersion to dry quickly. After that, the titanium oxide and silicon oxide composite dispersion prepared in step (2) is added dropwise at a rate of 80 g / m 2 After being spin-coated by a nylon fiber wheel, a ceramic tile product with high-efficiency photocatalytic ability is finally obtained.
[0036] Comparative Example 1
[0037] A ceramic tile, the preparation method of which comprises the following steps: mixing gas-phase nano titanium oxide (average particle size 20 nm, 85% anatase and 15% rutile phase mixed crystal form), aqueous hyperdispersant (model AKN-2300), and deionized water in a mass ratio of 10:3:87, obtaining a milky white opaque titanium oxide dispersion after high-speed shear stirring, and then spin-coating the dispersion on the surface of the glazed ceramic tile after surface polishing in a waxing machine, with a drop amount of 70 g / m 2 , and obtain the ceramic tile.
[0038] Comparative Example 2
[0039] A ceramic tile, the preparation method of which is different from that of Example 1 in that: in step (2), anionic silica sol (model JN15-25, solid content of 25%, average particle size of 15 nm) is used instead of cationic silica sol; the rest is the same as that of Example 1.
[0040] Comparative Example 3
[0041] A ceramic tile, the preparation method of which comprises the following steps:
[0042] (1) Self-dispersed nano-anatase titanium oxide powder with an average particle size of 10 nm was mixed with deionized water at a mass ratio of 15:85, and a translucent monodispersed titanium oxide dispersion with a solid content of 15% was obtained after stirring;
[0043] (2) The glazed ceramic tile with polished surface was used as the ceramic tile body. The prepared 15% titanium oxide dispersion was first polished and spun onto the tile surface using a nylon fiber wheel in a waxing machine. The amount of the dispersion was 60 g / m 2 The fiber wheel quickly rubs against the brick surface to generate a higher temperature, which enables the dispersion to dry quickly, and finally the ceramic brick product is obtained.
[0044] Comparative Example 4
[0045] A ceramic tile, the preparation method of which comprises the following steps:
[0046] (1) Self-dispersed nano-anatase titanium oxide powder with an average particle size of 10 nm, cationic silica sol (solid content 25%, average particle size 10 nm), silicone hydrophilic modifier (epoxy polyether modified polysiloxane), aqueous acrylic resin aqueous solution (solid content 42%) and deionized water were mixed and stirred in a mass ratio of 3:48:3:7.14:38.86 to obtain a titanium oxide and silicon oxide composite dispersion with a titanium oxide mass concentration of 3%, a silicon oxide mass concentration of 12%, a silicone hydrophilic modifier mass concentration of 3% and an acrylic resin mass concentration of 3%;
[0047] (3) The glazed ceramic tile with polished surface was used as the ceramic tile body. The prepared titanium oxide and silicon oxide composite dispersion was added in a waxing machine using a nylon fiber wheel at a rate of 60 g / m 2 After being spin-coated by a nylon fiber wheel, the ceramic tile product is finally obtained.
[0048] Comparative Example 5
[0049] A ceramic tile, the preparation method of which is different from that of Example 1 in that: no organosilicon hydrophilic modifier is added in step (2); the rest is the same as that of Example 1.
[0050] Comparative Example 6
[0051] A ceramic tile, the preparation method of which is different from that of Example 1 in that: no aqueous acrylic resin solution is added in step (2); the rest is the same as that of Example 1.
[0052] Comparative Example 7
[0053] A ceramic tile, the preparation method of which is different from that of Example 1 in that: no aqueous acrylic resin solution is added in step (2), and after step (3) is completed, a hydrophobic organic silicon antifouling agent (commonly known as 3# waterproofing agent) is coated on the surface; the rest is the same as that of Example 1.
[0054] Effect Experiment
[0055] The present invention adopts two testing methods to evaluate the photocatalytic degradation ability of the photocatalytic ceramic.
[0056] The first method is to measure the degradation ability of photocatalytic ceramic tiles on simulated pollutant methylene blue solution. The test method refers to ISO10678:2010. The concentration of methylene blue solution is 10 μmol / L, the wavelength of the light source is 395 nm, the power is 45 W, the illumination time is 24 h, the contact surface between the methylene blue solution and the brick surface is a circle with a diameter of 80 mm, and the addition amount is 20 mL. The degradation rate of methylene blue is calculated by measuring the absorbance of the methylene blue solution before and after illumination. This test method is simple to operate and reliable in measurement, and can be used for daily test evaluation.
[0057] The second test method is to directly measure the degradation of acetaldehyde gas by photocatalytic ceramic tiles in accordance with the method of GB / T 23761-2020 "Test method for air purification performance of photocatalytic materials and products - Degradation of acetaldehyde (or formaldehyde)", simulating the degradation process of harmful gases in real use scenarios. The test light source is ultraviolet light with an irradiation intensity of 1.0 mW / cm 2 .
[0058] In order to test the durability of the photocatalytic coating, the samples were subjected to a scrub resistance test on a multifunctional scrub resistance tester. The principle is to use a specific friction head to perform linear reciprocating friction on the test sample. In this test, a sponge head was used. When scrubbing, a detergent solution was used to keep the brick surface moist. The test was scrubbed 1,000 times in total. After the test was completed, the photocatalytic degradation ability test was performed. In addition, in order to examine the durability of the hydrophilic state of the sample surface, the sample was placed outdoors for a weather resistance test. The test period was 14 days, and the wetting angle of the brick surface before and after the test was tested.
[0059] The ink contamination resistance test process is to apply blue-black ink to the sample surface, leave it on for 20 minutes, then rinse it with clean water and observe the ink residue.
[0060] The results are shown in Tables 1, 2 and Figure 3 (Measurement results of the surface wetting angle of the ceramic tile prepared in Example 1) are shown.
[0061] Table 1 Degradation performance test results of examples and comparative examples
[0062]
[0063] Table 1 shows the relevant test data of the photocatalytic degradation ability, pollution resistance and durability of the samples of the embodiments and comparative examples. It can be found that in comparative example 1, due to the use of conventional titanium oxide nanopowder, the dispersion liquid is milky white due to poor dispersibility, which affects the clarity of the color texture of the brick surface to a certain extent after being applied to the brick surface. In comparative example 2, due to the incompatibility between the anionic silica sol and the self-dispersed nano titanium oxide used, the composite dispersion liquid gels, resulting in the inability to evenly apply on the brick surface, causing the brick surface to be rough and hazy locally; in other test examples, self-dispersed nano titanium oxide or more compatible cationic silica sols are used, and the surface color texture of the samples is clear. More importantly, they all show a higher methylene blue degradation rate, which is higher than 43% in comparative example 1. Since a single-layer coating structure is used in comparative example 4, the surface titanium oxide loading is relatively low, thereby reducing its degradation rate to a certain extent; in comparative example 3, due to the use of a single-layer self-dispersed titanium oxide coating structure, its coating will dissolve again after encountering water, making it impossible to carry out the methylene blue degradation test.
[0064] The addition of the hydrophilic modifier and the water-based acrylic resin enables the samples (Example 1, Example 2, Comparative Example 4) to have the same excellent anti-fouling ability as the conventional silicone anti-fouling agent (Comparative Example 7), while also showing good durability, maintaining a high pollutant degradation ability after being scrubbed a thousand times.
[0065] Since both silicon oxide and titanium oxide coatings are extremely hydrophilic, the corresponding samples (except samples in comparative example 7) all exhibit extremely low wetting angles (not higher than 10°). However, the addition of hydrophilic modifiers allows the samples to maintain excellent hydrophilicity after weather resistance testing, such as Example 1, Example 2, Comparative Example 2, Comparative Example 4, and Comparative Example 6, which is very beneficial for maintaining its efficient ability to degrade air pollutants.
[0066] Table 2 Test data of photocatalytic samples' ability to degrade acetaldehyde gas
[0067]
[0068] Table 2 shows the degradation ability of Example 1 and Comparative Example 7 samples for acetaldehyde gas. It can be found that the example samples have higher photocatalytic degradation ability due to the super hydrophilic characteristics of the surface, indicating that compared with the hydrophobic surface in Comparative Example 7, the addition of hydrophilic modifiers and non-hydrophobic acrylic antifouling agents can make the samples have excellent air pollutant degradation ability.
[0069] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.
Claims
1. A ceramic tile with photocatalytic function, characterized in that: The ceramic tile body and the first photocatalytic coating and the second photocatalytic coating are sequentially arranged on the surface thereof, wherein the first photocatalytic coating is self-dispersed nano-anatase titanium oxide, and the second photocatalytic coating includes silicon oxide and self-dispersed nano-anatase titanium oxide; The second photocatalytic coating is formed by spin-coating a composite dispersion on the surface of the first photocatalytic coating, and the ceramic tile with photocatalytic function is obtained after spin-coating; The composite dispersion liquid consists of cationic silica sol, self-dispersed nano anatase titanium oxide, organic silicon hydrophilic modifier, water-based acrylic resin and water.
2. The ceramic tile with photocatalytic function according to claim 1, characterized in that: The organosilicon hydrophilic modifier is polyether-modified polysiloxane.
3. The ceramic tile with photocatalytic function according to claim 1 or 2, characterized in that: The average particle size of the self-dispersed nano-anatase titanium oxide is 3 nm-10 nm.
4. A method for preparing a ceramic tile with photocatalytic function as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: A titanium oxide dispersion is spin-coated on the surface of the ceramic tile body to form the first photocatalytic coating, and then a composite dispersion is spin-coated on the surface of the first photocatalytic coating to form the second photocatalytic coating; the titanium oxide dispersion is obtained by mixing self-dispersed nano-anatase titanium oxide with water, and the composite dispersion is composed of self-dispersed nano-anatase titanium oxide, cationic silica sol, silicone hydrophilic modifier, water-based acrylic resin and water.
5. The preparation method according to claim 4, characterized in that: The solid content of the titanium oxide dispersion is 3%-15%, and the coating amount is 30 g / m 2 -50 g / m 2 .
6. The preparation method according to claim 4, characterized in that: The solid content of the cationic silica sol is 20%-30%.
7. The preparation method according to claim 4, characterized in that: In the composite dispersion, the mass concentration of titanium oxide is 1%-5%, the mass concentration of silicon oxide is 6%-15%, the mass concentration of organic silicon hydrophilic modifier is 1%-3%, and the mass concentration of waterborne acrylic resin is 3%-5%. The coating amount of the composite dispersion is 40 g / m 2 -80 g / m 2 .
Citation Information
Patent Citations
A method and apparatus for preparing monodisperse nano-titanium dioxide
CN113896235B
Titanium dioxide photocatalyst and preparation method and application thereof in ceramic tiles
CN111792670A
Zirconium-modified cationic silica sol and preparation method thereof
CN113135573A
Titanium dioxide photocatalytic self-cleaning coating, coating and preparation method of titanium dioxide photocatalytic self-cleaning coating
CN116925634A